Violence in schoolchildren: A study on gender identity and violence through artistic representations. - Martínez Cano, Silvia (Pulso. Revista de educación, 2008)
This article gathers the conclusions of a study on the role of gender and personal identity in the manifestation and support of violence in the school context. The research lies on gender as a conceptual base and on the graphic expression of children as a means of communication. Through it, we aim at contrasting and determining behavior patterns and attitude models which are at the core of violence, subordination, and the underestimation of women since childhood. The graphic material of the present research is a rich source which allows for comparing and discriminating patterns based on gender violence which may be repetitive along time. From this point we aim at deconstructing and creating new models of relationship of gender, thus preventing the apparition of violence.
Keywords: Gender Based Violence; Gender Identity; Children´s Drawing; Graphical Representation; Education